KUALITAS PELAYANAN PUBLIK DI KANTOR PENGADILAN AGAMA BULUKUMBA - Sukarna, Ayuni; Sofyan, Sofyan (Siyasatuna: Jurnal Ilmiah Mahasiswa Siyasah Syar'iyyah, 2023)
Court services are activities or a series of activities in the framework of meeting the needs of services for the community, especially justice seekers, provided by the Supreme Court and the judicial bodies under it based on laws and regulations and the principles of public service. The purpose of this study was to determine the form of service at the Bulukumba Religious Court Office. The method used in this research is a qualitative field research with a normative juridical approach. The results of this study indicate: 1) The services of the Bulukumba Religious Court are trial administration services, legal aid services and complaints and information requests. 2) The quality of public services at the Bulukumba Religious Court has been going quite well with the provision of various adequate facilities, clear trial procedures and other completeness of infrastructure.